Digital Supply Chain: Is It Important For Enhancing Supply Chain Performance? - Danandjojo, Aditya; Juliawan, Freshe; Kurniawati; Masnita, Yolanda (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
A supply chain based on technology is very important in Industry 4.0. Unfortunately, several manufacturing companies have not been using optimally this technology. However, big manufacturing companies are. This paper proposes a solution providing good insight based on the digital supply chain. The aim of this study is to provide acceptable digital supply chain implementation, especially for manufacturing companies which still not using the technology in their supply chain process. This research used RBV theory in order to compare the prior study with the current situation. In this research, all the variable studies are positively affecting the supply chain performance. In this study, the implementation of digital supply chain can improve supply chain performance by combining with supply chain quality management practices. Especially with Supply chain agility as a mediating process.